ISPRING APPLICATION OF THE NUMBER THING ATHLETIC MATERIALS FOR JUNIOR HIGH SCHOOL PHYSICAL EDUCATION TEACHER - Khusnul Khotimah; Ari Wibowo Kurniawan (Universitas Negeri Medan, 2023)
Development of learning by using tools or tools that are useful for improving learning and conveying information. The purpose of this research is to develop learning based on throwing material applications for middle school PJOK teachers in Pasuruan Regency. This research and development learning method uses a research and development method by following seven steps. By using a quantitative descriptive study and using percentages, the results of the study of data from learning experts get a percentage of 88,5%, throw learning experts 87,5%, media experts 98,5%, and involving 36 middle school PJOK teachers in Pasuruan Regency. The small group trial was distributed to 11 respondents and the large group distributed to 25 respondents obtained the results of 92,25% small group and 83,5% large group. Based on these data it can be concluded that this application based learning development product for throwing materials is very valid and suitable for use by PJOK SMP teachers.